Answer:
-4
<em>BRAINLIEST, PLEASE!</em>
Step-by-step explanation:
-12/3 = -4
First, we need to solve for the common ratio from the data given by using the equation.
a(n) = a(1) r^(n-1)
15 = -3 r^(2-1)
-5 = r
r = -5
Then, we can find the sum by the expression:
S(n) = a(1) ( 1 - r^n) / 1-r
S(8) = -3 (1 + 5^8) / 1+5
S(8) = -195313
Answer:
x=17
Step-by-step explanation:
well the triangles are congruent so that equation has to equal 61, so set it equal to 61, once you do that subtract 10 with 61 giving you 51, then divide 3 with 51 and you get 17
![3x + 10 = 61 \\ 3x = 51 \\ x = 17](https://tex.z-dn.net/?f=3x%20%2B%2010%20%3D%2061%20%5C%5C%203x%20%3D%2051%20%5C%5C%20x%20%3D%2017)
you have the hypotenuse and the opposite side so you will use sin
sin58= (30/q)
multiply both sides by q
q(sin58)=30
divide by sin58 in your calculatior
q=(30/sin58)
^ I don't have a calculator with me so you will need to plug that in
<span>89 is the correct answer.
</span>